Perceptions of Peruvian women on the digital photographic manipulation of the female body in advertisements - Miranda-Pelaez, Milagros (2024)
This study analyzes the perception of young Peruvian women between 23 and 33 years of age, graduates of a private university in Lima, Peru, on the manipulation of photographic images of the female body in advertising, based on stereotypes of beauty and male gaze in the campaign of the perfume J’adore by Dior. For this purpose, this study is positioned in the interpretative paradigm, qualitative approach with an ethnographic design. The information was collected through semi-structured interviews with 20 young women graduates of the Faculty of Communications and Administration. As a result, it was evidenced the excessive use of Adobe Photoshop, the conception of beauty, the aspirational image, among others. Therefore, it is suggested to continue with this line of research to know the perceptions of other study groups about male gaze and its relationship with photographic manipulation.